Autism Kits App: Interactive Mobile Game for Visual Impairment among Autism Spectrum Disorder - Ku Nuraini Che Ku Mohd, Che; Shahbodin, Faaizah; Adly Mohd Noor, Helmi; Suparjoh , Suriawati; Pramudya Ananta, Gede (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to report on the development of an Android based application using serious games technique. Autism Kits is a developed mobile application which will act as a learning-based application for autism spectrum disorder. ADDIE methodology has been applied in the development. The testing has been conducted to participants which consist of autism students, teachers and parents. A survey has been conducted after they have gone through the application. Results have shown that the teachers and parents are willing to use the application for autism student and the usage of mobile phones will benefit children with autism.